Effects of Students Perception and Motivation on Online Accounting Learning During the Covid-19 Pandemic: Empirical Evidence of Accounting Students in Indo Global Mandiri University - Eka Diana Sari; Lukita Tripermata; Muhammad Hamdan Sayadi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to determine the effect of student perceptions and motivation on online accounting learning in the Covid-19 pandemic era. The data were obtained from observations and distributing questionnaires to 76 students majoring in the accounting study program at Universitas Indo Global Mandiri Palembang class of 2017-2020. The collected data were analyzed using the multiple linear regression analysis methods. Further statistical tests revealed a positive influence between perception and motivation respectively and simultaneously on online accounting learning in the era of the Covid-19 pandemic. Furthermore, the results show the coefficient of determination (R2) obtained a value of 0.586. This proves that students' perceptions and motivation affect online accounting learning by 58.6%, the remaining is influenced by other variables not included in this study.